2007
DOI: 10.1007/s10798-007-9046-0
|View full text |Cite
|
Sign up to set email alerts
|

Technological literacy: a multliteracies approach for democracy

Abstract: Throughout history various grand narratives have impacted on technology education. In the current post modern era of globalization, technology education continues to struggle for relevance and definition, and takes various forms in different countries, but none seem resoundingly successful. The current development of what some have termed a digital democracy (Web 2.0)-the explosion of a new type of information technology which has become an integral characteristic of young people's lives, is the starting point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 10 publications
0
21
0
4
Order By: Relevance
“…In spite of the clear distinctions between the nature of vocational and D&T education, it is debated whether or not practices in D&T have shifted in alignment with international discourse and policy changes (Banks and Barlex 1999;Dakers 2005a;Doyle et al 2017;Mittell and Penny 1997). Much of the contentions in understanding the evolution of practice from vocational to D&T education appear to have stemmed from the difficulties in explicating goals for D&T, as researchers in the discipline appear to broadly converge on either the concept of technological capability (Black and Harrison 1985;Gibson 2008;Kelly et al 1987;Kimbell 2011) or technological literacy (Dakers 2014a, b;Gagel 2004;Ingerman and Collier-Reed 2011;Petrina 2000Petrina , 2007Williams 2009). In discussing the differences between technological capability and technological literacy, Kimbell and Stables describe the contention between the terms as the "transatlantic dissonance" (2007, p. 22) in D&T education.…”
Section: The Nature Of Dandt Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the clear distinctions between the nature of vocational and D&T education, it is debated whether or not practices in D&T have shifted in alignment with international discourse and policy changes (Banks and Barlex 1999;Dakers 2005a;Doyle et al 2017;Mittell and Penny 1997). Much of the contentions in understanding the evolution of practice from vocational to D&T education appear to have stemmed from the difficulties in explicating goals for D&T, as researchers in the discipline appear to broadly converge on either the concept of technological capability (Black and Harrison 1985;Gibson 2008;Kelly et al 1987;Kimbell 2011) or technological literacy (Dakers 2014a, b;Gagel 2004;Ingerman and Collier-Reed 2011;Petrina 2000Petrina , 2007Williams 2009). In discussing the differences between technological capability and technological literacy, Kimbell and Stables describe the contention between the terms as the "transatlantic dissonance" (2007, p. 22) in D&T education.…”
Section: The Nature Of Dandt Educationmentioning
confidence: 99%
“…Despite theoretical approaches to conceptualising a model for enactment Moreland 2003, 2004), and applied approaches to measuring PCK through multiple choice questionnaires (Rohaan et al 2009(Rohaan et al , 2012, the relationship between PCK and practice in the discipline is not necessarily understood. Williams, Lockley, and Mangan (2016) suggested that the degree of international diversity regarding the content of D&T may have served as an impediment to the development of research in the area, as the implicit nature of knowledge (Kimbell 2011;Williams 2009) is theorised to have a significant impact on enacted practice. Cognisant of the difficulties in understanding the relationship between PCK, teacher beliefs, and practice in science and mathematics education, and the complex nature of knowledge in D&T education, it is theorised that the application of current frameworks to D&T may be premature as the potential for variability in application is increased.…”
Section: Introductionmentioning
confidence: 99%
“…Dewasa ini beragam jenis informasi tersebut (teks, gambar, video) bisa disampaikan melalui teknologi internet yang menciptakan dunia baru bagi manusia, yakni dunia online yang memproduksi pola-pola interaksi sosial baru tanpa mengenal batas-batas geografis, administratif, dan sekat-sekat lainnya. Dunia internet, misalnya Web 2.0, memiliki ciri: open communication, decentralization of authority, freedom to share and re-use, user's ownership of data, dan an effectiveness of communication (Williams, 2009). Ketika sebuah informasi diformat dalam bentuk digital, maka ia bisa dimanipulasi (direplikasi, ditransformasikan, dan dikomunikasikan) (Ensmenger, 2012).…”
Section: Tinjauan Pustakaunclassified
“…Technology education has seen significant change in its philosophy and content (Williams, 2009) which has, at times, led to a disjunction between Technology in the New Zealand Curriculum (MoE, 2007) as espoused by the Ministry of Education, and the practice being enacted in some schools. In his writing about the philosophy of technology, de Vries (2012) indicated that this could be attributed to some technology teachers who found a change in thinking and content challenging because they were "practical people who like to do practical things in class" (p. 15).…”
Section: Introductionmentioning
confidence: 99%